A case of symptomatic Rathke's cyst. (25th January 2013) - Naik, Vismay Dinesh; Thakore, Nilay Rajendra
Abstract : Rathke's cleft cyst is a benign growth found on the pituitary gland in the brain, specifically a fluid-filled cyst in the posterior portion of the anterior pituitary gland. It occurs when the Rathke's pouch does not develop properly, and ranges in size from 2 to 40 mm in diameter. Asymptomatic cysts are common, detected during autopsies of 2–26% of individuals who have died of unrelated causes. Symptomatic cysts are rare and only approximately 150 cases have been reported. Females are twice as likely as males to have a cyst. Symptomatic cysts can trigger visual disturbances, pituitary dysfunction and headaches. Here we present a case of a 40-year-old female patient who presented with complains of visual disturbances, headache and amenorrhoea. On investigations, MRI of brain revealed findings suggestive of Rathke's cleft cyst.